Early Learning Issues in Philippi, Cape Town: Caregivers’ Concerns, Satisfaction, Subjective Affordability and Perceptions - Siphe Madyibi; Amiena Bayat (Indonesian Journal of Early Childhood Education Studies, 2024)
Despite its known contribution to later educational outcomes, early learning needs to be better conceptualized, understood, and appreciated by caregivers, who arguably know little about early learning. Caregivers of low socioeconomic status have limited access to quality ECD facilities and are less able to guide their children’s early learning. Reasoning that positive change should reflect caregivers' views, concerns, and knowledge, the researchers engaged with a sample of 40 caregivers in Philippi, a low-income area in Cape Town, about their problems, satisfaction, subjective affordability, and perceptions of early learning at the ECD facilities attended by their children. The study employed a multiple-case study design, following a qualitative-dominant research methodology. The study found that most caregivers were satisfied with the ECD facilities attended by their children but had reservations about quality, with some doubting the facilities' ability to provide meaningful early learning experiences to their children. Although their reasons differed, most caregivers understood ECD's importance in school readiness, early learning, and non-cognitive skills (socialization). Most caregivers struggle to afford the cost of early learning, whether in a registered or unregistered ECD facility. This suggests that expanded state funding of ECD is urgently required.